Literature study: various abilities of high school students obtained from the application of problem-based learning models in the field of natural science - Rizki Anissa Putri Suprihadi; Destri Ratna Ma rifah (Universitas Ahmad Dahlan, 2022)
One of the capabilities of 21st-century education is to improve critical thinking skills. However, what happens in the field is that high school students' critical thinking skills are still low. Therefore, a learning model is needed that has the potential to improve critical thinking skills. The model is Problem Based Learning (PBL). This study aims to determine what abilities are obtained from the application of Problem Based Learning (PBL) and modified PBL learning models. This type of research is a literature study with a narrative review design. Presentation of data using tables and data analysis using descriptive analysis. The articles obtained were 36 articles related to the PBL model and critical thinking skills. The results showed that the modified PBL and PBL learning models could improve other abilities, such as understanding and mastery of material concepts, student activity, student learning outcomes, scientific thinking skills, problem-solving abilities, and creative thinking skills.